Using community engagement to adapt anxiety cognitive behavioural therapy for autistic youth receiving services in Michigan community-based organisations: protocol for a mixed methods study - Amy Drahota; Jessica Tschida; Izza Peeran (BMJ Open)
Introduction Anxiety disorders are among the most common co-occurring mental health conditions experienced by autistic youth. Without appropriate intervention, anxiety disorders and related difficulties experienced by autistic youth can remain well into adulthood, causing reduced quality of life. Behavioral Interventions for Anxiety in Children with Autism (BIACA) is a manualised, modular evidence-based cognitive behavioural therapy with demonstrated efficacy in reducing or fully remitting anxiety symptoms and improving overall adaptive functioning for autistic youth. However, BIACA has been developed and tested mostly in academic research laboratories and has involved a limited number of community clinicians. Thus, certain characteristics (eg, length, complexity) may require adaptation to facilitate adoption and use in community settings.Methods and analysis This mixed methods study will use and evaluate a community-engaged, intervention adaptation method (ie, Adapted version of the Method for Program Adaptation through Community Engagement (AM-PACE)) to develop an adapted version of BIACA for community use. In the current study, the AM-PACE method will involve: (1) a Community Advisory Board (CAB), (2) structured process to identify core components, (3) community feedback via surveys and semistructured interviews and (4) role play exercises with intended clients. Thereafter, community-based providers (N=200) will be asked to evaluate the feasibility, acceptability, appropriateness, usability and intent to use for the original BIACA intervention and adapted BIACA intervention. Repeated measures Analysis of Variance (ANOVA) will be conducted to determine whether programme type predicts provider ratings. Higher provider ratings for the adapted BIACA intervention may indicate adaptations identified through AM-PACE-enhanced potential for BIACA to be equitably implemented in community settings.Ethics and dissemination Ethics approval was obtained from the Michigan State University Institutional Review Board. Research findings will be published in peer-reviewed journals, presented at international conferences and disseminated in alignment with CAB recommendations.Registration This study has been registered on Open Science Framework: https://doi.org/10.17605/OSF.IO/Z54MD